Pokémon : Power Up Psyduck [anglicky]. Book 7 - West, Tracey, 1965- (Orchard Books, 2021)
Psyduck's powers can blow Team Rocket out of the water, but it isn't the easiest Pokémon to look after...Join the Pokémon-masters-in-training as they learn all about Psyduck's unique history, from when he first met Misty to his latest challenge - a battle like no other.